O impacto de tarefas de tradução na identificação de ideias principais do texto nas aulas de inglês do ensino básico da rede pública - Silva, Angelisa Evelyn Alves da (2020)
English teaching in Brazil has had a series of distinct phases from its beginning to the present day, as new research on approaches and methodologies is disseminated every moment. However, a lot has been discussed about the methodologies and approaches for Foreign Language (FL) teaching, mainly about the applicability of translation in public schools. To demystify the use of translation in the FL classroom, we have the support of theoreticians such as Atkinson (1993), Romanelli (2009) e Balboni (2011), who even in the context of the communicative approach endorse translation as an instrument of pedagogical support. The exercise of reading is an indispensable action and constitutes one of the primordial factors for the acquisition of knowledge. We believe that learning and teaching reading comprehension are complex and challenging processes for students and teachers at schools. Understanding can be enhanced by using conscious techniques to solve comprehension problems. These strategies help the student to perform an autonomous reading, SOLÉ (1998). This way, the objective of this study is to analyze the impact of translation in the identification of the main ideas of the text in the English classes of a public basic education school, aiming to test reading comprehension through main ideas, and how translation can be used as a support tool in the process of teaching and learning English. As methodological procedure to verify the hypothesis of this study which is “The use of translation to identify the main ideas of the text in English contributes to a better understanding of the text”, eight students from the public school were invited to participate voluntarily., eight students from the public school were invited to participate voluntarily. Four tasks and a questionnaire were used after completing the last task. Tomitch (1995; 1996) points out that the identification of the main idea is one of the most important skills in reading comprehension. The analysis of main idea identification was based on three types of evaluation (full, partial and none) and the responses of the participants for each text were scored according to the criteria established by Torres, 1998. Through this experiment, the effectiveness of the translation on the identification of the main ideas of the text was verified, aiming to test if there were improvements on the reading comprehension of the students, since the pedagogical translation was used as a support tool for learning a foreign language.